2014
DOI: 10.1093/jxb/eru462
|View full text |Cite
|
Sign up to set email alerts
|

TaHsfA6f is a transcriptional activator that regulates a suite of heat stress protection genes in wheat (Triticum aestivum L.) including previously unknown Hsf targets

Abstract: SummaryA wheat HsfA6 member acts as a transcriptional activator for up-regulation of a suite of heat stress protection genes including previously unknown Hsf targets such as Golgi anti-apoptotic protein.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
74
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 150 publications
(78 citation statements)
references
References 85 publications
4
74
0
Order By: Relevance
“…Activities of SOD, APX and CAT in transgenic chrysanthemum overexpressing CmHsfA4, were higher than those of WT lines under salt stress . In addition, Hsf activates the expression of downstream genes (including Hsps) and shows a similar pattern of expression to protect plants from external stress (Snyman and Cronjé, 2008;Xue et al, 2014;Xue et al, 2015;Chen et al, 2018). In the present study, we also observed that transgenic Arabidopsis and NHE S. alfredii expressing SaHsfA4c showed higher CAT, POD, and APX activities than those of the WT after Cd stress, and were able to induce the expression of ROS-scavenging system related genes (POD, CAT and APX) and Hsps.…”
Section: Discussionsupporting
confidence: 77%
“…Activities of SOD, APX and CAT in transgenic chrysanthemum overexpressing CmHsfA4, were higher than those of WT lines under salt stress . In addition, Hsf activates the expression of downstream genes (including Hsps) and shows a similar pattern of expression to protect plants from external stress (Snyman and Cronjé, 2008;Xue et al, 2014;Xue et al, 2015;Chen et al, 2018). In the present study, we also observed that transgenic Arabidopsis and NHE S. alfredii expressing SaHsfA4c showed higher CAT, POD, and APX activities than those of the WT after Cd stress, and were able to induce the expression of ROS-scavenging system related genes (POD, CAT and APX) and Hsps.…”
Section: Discussionsupporting
confidence: 77%
“…Plant adaptation to high-temperature environments requires transcriptional reprogramming of a series of genes involved in heat stress protection (Xue et al, 2015). HSPs are a family of target genes of HSF, some of which are known to act as chaperones preventing misfolding and aggregation of other proteins during heat stress (von .…”
Section: Discussionmentioning
confidence: 99%
“…A similar modulation of HSFs and HSPs was found in tomato in response to heat, drought and salinity (Fragkostefanakis et al ., ). In wheat, overexpression of Triticum aestivum HSFA6f was demonstrated to direct the expression of several HSPs , leading to thermotolerance (Xue et al ., ). Most strikingly, the expression of a maize HSF , ZmHSF06 ( Zea mays HSF06 ), is sufficient to confer heat and drought stress resistance to Arabidopsis (Li et al ., ).…”
Section: Introductionmentioning
confidence: 97%